2020
DOI: 10.1016/j.bjpt.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Baseline characteristics did not identify people with low back pain who respond best to a Movement System Impairment-Based classification treatment

Abstract: Study design: Secondary analysis of data from a randomized controlled trial. Background: Treatment based on the Movement System Impairment-Based classification for chronic low back pain results in the same benefit when compared to other forms of exercise. It is possible that participant's characteristics measured at baseline can identify people with chronic low back pain who would respond best to a treatment based on the Movement System Impairment model. Objectives: To assess if specific characteristics of peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…For prognosis, STarT Back classification for improving pain or disability is shown in Supplementary Table 4 . Of these, 17 studies assessed pain and disability prognosis with univariate models 70 , 74 , 77 , 80 , 81 , 84 86 , 89 , 94 , 96 , 97 , 104 – 108 . Of the univariate analyses, eight showed significant prognostic benefits for pain intensity 74 , 83 , 85 , 89 , 93 , 97 , 106 , 107 , 13 showed significant prognostic benefits for disability 74 , 83 86 , 89 , 93 , 94 , 96 , 97 , 102 , 105 , 108 , while two showed significant prognostic benefits on mixed pain intensity and disability analyses 80 , 81 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For prognosis, STarT Back classification for improving pain or disability is shown in Supplementary Table 4 . Of these, 17 studies assessed pain and disability prognosis with univariate models 70 , 74 , 77 , 80 , 81 , 84 86 , 89 , 94 , 96 , 97 , 104 – 108 . Of the univariate analyses, eight showed significant prognostic benefits for pain intensity 74 , 83 , 85 , 89 , 93 , 97 , 106 , 107 , 13 showed significant prognostic benefits for disability 74 , 83 86 , 89 , 93 , 94 , 96 , 97 , 102 , 105 , 108 , while two showed significant prognostic benefits on mixed pain intensity and disability analyses 80 , 81 .…”
Section: Resultsmentioning
confidence: 99%
“…For prognosis, STarT Back classification for improving pain or disability is shown in Supplementary Table 4. Of these, 17 studies assessed pain and disability prognosis with univariate models 70,74,77,80,81,[84][85][86]89,94,96,97,[104][105][106][107][108] . Of the univariate analyses, eight showed significant prognostic benefits for pain intensity 74,83,85,89,93,97,106,107 , 13 showed significant prognostic benefits Azimi et al 22 1 1 1 1 0 0 0 1 0 5 / 9 Barons et al 52 1 1…”
Section: Start Back Toolmentioning
confidence: 99%
“…Thus, baseline characteristics of individuals would be useful to predict the differential response to intervention strategies. Previous research has found that baseline clinical and demographic factors influence treatment response, but these characteristics have not achieved the accuracy required for prediction ( Underwood et al, 2007 ; Azevedo et al, 2019 ; Witt et al, 2019 ). Some studies have focused on quantitative sensory testing (QST) in the prediction of analgesic effects, but with contradictory results ( Grosen et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%